A Brochure For ABC Christian Elementary School - Magdalena Felicia (Kata Kita: Journal of Language, Literature, and Teaching, 2018)
Promotional tools are crucial in helping a company to promote them. Brochure is what ABC Christian Elementary School need right now to help them promote their school during the open house and education fair. ABC Christian Elementary School’s target market are middle upper class people. They do not have brochure for their elementary school and this has created problems during the education fair and open house. Therefore, I make them a brochure in Indonesian and English version as effective and informative promotion tools. This way the school can attract more potential customers to join the school.